Encyclopedia Brown gets his man - Sobol, Donald J.; Shortall, Leonard (New York : Puffin Books, 2007)
Ten brief cases in which the reader pits his wits against those of Encyclopedia Brown, an ingenious twelve-year-old detective.
Ages 7 up.
Keywords: Detective and mystery stories; Detective and mystery fiction